Prioritization of Key Qualification Indicators related to Operational-Level Managers based on Multiple Criteria Decision Making, Fuzzy TOPSIS in Tehran University of Medical Sciences - Ali Moradi; KHaled Rahmani; Ebrahim Jaafaripooyan; Rasoul Yarahmadi (Tehran University of Medical Sciences, 2018)
Introduction: Since incorrect selection of  a manager might lead to incorrect choices of other members, organizations need to consider this important issue  and use well-sought mechanisms for managers' selection process. Accordingly, this study aims to rank the key factors associated with the selection of operational managers in Tehran University of Medical Sciences.   Materials and Methods: This research employed a logical and systematic trend to develop and rank the indicators using fuzzy TOPSIS method. In order for prioritization of key indicators of qualification of operational-level;  after reviewing the literature and using experts' viewpoints , the dimensions of performance have been selected and using, the SMART technique the key criteria were weighted. A validated and reliable questionnaire was used for data collection.   Results: Fifty individuals participated in this study. 37 (74%) and 13 (26%) were male and female respectively. The mean and standard deviation of age of participants were 41.68 and 7.06 years. Literature reviews and related studies indicated 48 indices  for choosing qualified managers. Among these, according to the  expert's opinion in management science and managers, 36 indices were selected as key indicators. Based on the FTOPSIS analysis, indicators of higher education in the field of management, compliance time, power of expression, adornment and belief in law and order achieved coefficients as 0.205, 0.204, 0.203, 0.202 and 0.197, rank first to fifth.   Conclusion: According to the results management related education and expertise in technical aspects of organizational management control  were at the top of ranking . Results of this study can help  medical universities and health service organizations to develop guidelines for selecting their managers.